Ruptures : Anthropologies of Discontinuity in Times of Turmoil - Sauma, Julia; Kapferer, Bruce; Holbraad, Martin (Book collections on Project MUSE., 2019)
Ruptures brings together leading and emerging internationalanthropologists to explore the concept of 'rupture'.